Arterial Blood Gas Analysis and Dyselectrolytemia in Acute Exacerbation of Chronic Obstructive Pulmonary Disease (COPD) - Reddy, Nivedita Tayamgol; Patil, Sachin; Reddy, Kailash (International Journal of Integrated Health Sciences, 2025)
Background: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) is one of the important causes of  morbidity, mortality, and healthcare burden. Electrolyte disturbances and acid–base imbalances are frequent but under-recognized complications that may worsen outcomes in cases of AECOPD.Objective: To understand the prevalence of serum electrolyte abnormalities and arterial blood gas (ABG) parameters in patients admitted with AECOPD.Methods: This prospective observational study enrolled 200 patients with confirmed AECOPD admitted to a tertiary care hospital in Kalaburagi, India, over an 18 month period. The ABG analysis and serum electrolytes (sodium, potassium, magnesium, chloride) measurement were performed at admission. Demographic, clinical, and radiological data were also collected. Data were then analyzed using SSPS 23.0, with a P value of < 0.05 considered statistically significant.Results: Abnormalities related to sodium (91.5%), potassium (90.5%), magnesium (80.5%), and chloride (56%) were common in cases admitted with AECOPD. In 45% cases, the PaO₂ <50 mmHg  was seen whereas PaCO₂ >45 mmHg was found in 43%. Acid–base imbalance was seen  in 35% cases, with 4.5% showing severe acidosis (pH ≤7.1). Cough (72.5%) and breathlessness (60.5%) were most common symptoms. The majority were elderly males (65%) whereas 57% were smokers. Diabetes was the most common comorbidity (30.5%).Conclusion: Electrolyte abnormalities and ABG derangements are nearly universal in AECOPD and have important prognostic implications. Routine metabolic profiling should be integrated into the acute management of COPD to improve outcomes, particularly in resource-constrained settings.